Reckless Endangerment - Tanenbaum, Robert K. (New York A Signet Book, 1999)
Three crimes linked by a single cryptic message. Three crimes that will plunge an entire city into an explosive urban nightmare. Three crimes whose far-reaching consequences wikk touch Butch Karp and his family in the most intimate, unexpected, and terrifying ways imaginable.
Keywords: Fiction